Efeito da modalidade e intensidade do exercício sobre varoáveis hemodinâmicas e funcionais de idosos - Falcão, Guilherme Moreno [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Hypertension is a multifactorial and silent disease that affects millions of people around the world and is one of the major causes of the increase of cardiovascular impairment rates in adults, decrease of the quality of life and increase of mortality although today we have arranged several types of treatments that may mitigate the risks caused by the disease and treat the cardiovascular health of the affected patients. In addition to known treatments with drugs we have proven research that reveals the importance of lifestyle change for the control of cardiovascular diseases, improvement of physical capacity and quality of life in the population at risk. These changes are based on healthier eating habits, reduction of smoking and alcoholic beverages and especially the practice of physical exercise. The sedentary lifestyle is linked to the lack of physical activity practice by the population, either in physical training models, or in professional or leisure activity. The practice of physical activities is proven to be effective in reducing the risk of cardiac involvement due to arterial hypertension, so that through various physiological mechanisms imposed by the training demands the organism can respond acutely or chronically to the stimuli. The responses may be physiological such as: cardiometabolic adaptations, blood pressure control, resting heart rate control, increased blood perfusion in skeletal muscle, reduction of cholesterol and glycemic levels of individuals. Or improvement of the functional capacities like: improvement of strength and muscular power, flexibility and mobility. To obtain these answers, we can find today several intensities and protocols of aerobic, resistance or combined training that respond positively to these effects, and at the same time we find some protocols that can still be further explored to verify its relevance on the treatment... (Complete abstract electronic access below)

A hipertensão arterial é uma doença multifatorial e silenciosa que acomete milhões de pessoas ao redor do mundo e é uma das maiores causas do aumento dos índices de comprometimento cardiovasculares em adultos, diminuição da qualidade de vida e aumento da mortalidade embora hoje tenhamos disponíveis inúmeros tipos de tratamentos que podem amenizar os riscos causados pela doença e tratar da saúde cardiovascular dos pacientes acometidos. Além de conhecidos tratamentos com fármacos temos comprovadas pesquisas que revelam a importância da mudança do estilo de vida para o controle de doenças cardiovasculares, melhora da capacidade física e da qualidade de vida na população de risco. Essas mudanças são pautadas a partir de hábitos alimentares mais saudáveis, redução do fumo e bebidas alcoólicas e principalmente da prática de exercícios físicos. O sedentarismo está vinculado a falta de prática de atividade física pela população, seja em modelos de treinamento físico, seja em atividade profissional ou lazer. A prática de atividades físicas é comprovadamente eficaz para a redução dos riscos de comprometimento cardíaco pela hipertensão arterial, de forma que, por diversos mecanismos fisiológicos impostos pelas demandas de treinamento, o organismo pode responder aguda ou cronicamente sob os estímulos. As respostas podem ser fisiológicas como: adaptações cardiometabólicas, controle da pressão arterial, controle da frequência cardíaca de repouso, maior perfusão sanguínea no músculo esquelético, redução de níveis de colesterol e glicêmico dos indivíduos. Ou então melhora das capacidades funcionais como: melhora da força e potência muscular, flexibilidade e mobilidade. Para obtermos essas respostas, podemos encontrar hoje diversos intensidades e protocolos de treinamentos aeróbicos, resistidos ou combinados... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Envelhecimento; Exercícios físicos; Pressão arterial; Aging